You Read to Me, I'll Read to You - Hoberman, Mary Ann (Little, Brown Company, 2005)
This unique book in two voices uses traditional reading techniques-rhymes, rhymes, and repetition-to invite young children to read along with an adult$1! =s
Keywords: Poetry